2013
DOI: 10.1161/circresaha.113.301781
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cardiac L-Type Ca 2+ Channel Ca V 1.2 Via the β-Adrenergic-cAMP-Protein Kinase A Pathway

Abstract: Abstract:In the heart, adrenergic stimulation activates the β-adrenergic receptors coupled to the heterotrimeric stimulatory G s protein, followed by subsequent activation of adenylyl cyclase, elevation of cyclic AMP levels, and protein kinase A (PKA) activation. One of the main targets for PKA modulation is the cardiac L-type Ca 2+ channel (Ca V 1.2) located in the plasma membrane and along the T-tubules, which mediates Ca 2+ entry into cardiomyocytes. β-Adrenergic receptor activation increases the Ca 2+ curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(67 citation statements)
references
References 198 publications
(277 reference statements)
1
66
0
Order By: Relevance
“…This substantial reduction of basal Ca V 1.2 channel activity in STAA ventricular myocytes agrees with previous studies of these same Ca V 1.2 mutations expressed in nonmuscle cells (10). Many signaling pathways are thought to contribute to control of the basal activity of Ca V 1.2 channels in cardiac myocytes (30). Classic studies of PKA regulation of L-type Ca 2+ current in guinea pig ventricular myocytes showed that inhibition of PKA with excess regulatory subunit or the peptide PKI reduced basal Ca 2+ currents significantly.…”
Section: Phosphorylation Of Ser1700 and Thr1704 Is Required For Normasupporting
confidence: 91%
“…This substantial reduction of basal Ca V 1.2 channel activity in STAA ventricular myocytes agrees with previous studies of these same Ca V 1.2 mutations expressed in nonmuscle cells (10). Many signaling pathways are thought to contribute to control of the basal activity of Ca V 1.2 channels in cardiac myocytes (30). Classic studies of PKA regulation of L-type Ca 2+ current in guinea pig ventricular myocytes showed that inhibition of PKA with excess regulatory subunit or the peptide PKI reduced basal Ca 2+ currents significantly.…”
Section: Phosphorylation Of Ser1700 and Thr1704 Is Required For Normasupporting
confidence: 91%
“…The experiments presented here show that phosphorylation of this site is required for cardiac homeostasis and the prevention of heart failure in vivo. The mechanism of β-adrenergic/PKA stimulation of Ca V 1.2 channel activity in the fight-or-flight response has been controversial (7)(8)(9). However, the results of our previous experiments and those presented here leave no doubt about the importance of phosphorylation of Ser1700 in cardiovascular homeostasis and function.…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, an additional γ subunit is associated with the closely related Ca V 1.1 channels (11,12). Multiple PKA sites have been identified by phosphorylation of purified preparations of α 1 1.2 (Ser1928) and β (Ser459, Ser478, and Ser479) subunits; however, none of these sites is required for β-adrenergic regulation of Ca V 1.2 channels in cardiac myocytes in vivo or in transfected mammalian cells (7,8). In addition to channel phosphorylation, the formation of an autoinhibitory signaling complex is also essential for β-adrenergic regulation of Ca V 1.2 channel activity (7,13,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In human patients with Timothy syndrome, a G406R point mutation in Cav1.2 increases the channel activity and can lead to excessive insulin secretion and life-threatening hypoglycemia (Splawski et al 2004). PKA-dependent phosphorylation of Cav1.2 increases channel activity although the exact PKA site responsible for the regulation remains elusive (Weiss et al 2013). The potentiation of insulin secretion by cAMP is at least partially through PKA-mediated phosphorylation of Cav channels and increased Ca 2+ influx (Ammala et al 1993).…”
Section: Camp/pka In Pancreatic Isletsmentioning
confidence: 99%